Випадок первинного гіперальдостеронізму - Бурдо, І. С.; Тихонова, Н. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
This article discribes the case of primary hyperaldosteronism. Pathogenesis and treatment modalities are shown.